Translational Potential of Immune Tolerance Induction by AAV Liver-Directed Factor VIII Gene Therapy for Hemophilia A - Samelson-Jones, Benjamin J.; Arruda, Valder R. (Frontiers in Immunology, 2020)
Hemophilia A (HA) is an X-linked bleeding disorder due to deficiencies in coagulation factor VIII (FVIII). The major complication of current protein-based therapies is the development of neutralizing anti-FVIII antibodies, termed inhibitors, that block the hemostatic effect of therapeutic FVIII. Inhibitors develop in about 20-30% of people with severe HA, but the risk is dependent on the interaction between environmental and genetic factors, including the underlying F8 gene mutation. Recently, multiple clinical trials evaluating adeno-associated viral (AAV) vector liver-directed gene therapy for HA have reported promising results of therapeutically-relevant to curative FVIII levels. The inclusion criteria for most trials prevented enrollment of subjects with a history of inhibitors. However, preclinical data from small and large animal models of HA with inhibitors suggests that liver-directed gene therapy can in fact eradicate pre-existing anti-FVIII antibodies, induce immune tolerance, and provide long-term therapeutic FVIII expression to prevent bleeding. Herein, we review the accumulating evidence that continuous uninterrupted expression of FVIII and other transgenes after liver-directed AAV gene therapy can bias the immune system towards immune tolerance induction, discuss the current understanding of the immunological mechanisms of this process, and outline questions that will need to be addressed to translate this strategy to clinical trials.